2013
DOI: 10.1371/journal.pone.0074753
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-Adjuvanted Dendritic Cells Inhibit Tumor Growth and Metastasis: A Murine Model of Breast Cancer

Abstract: Tocotrienol-rich fraction (TRF) from palm oil is reported to possess anti-cancer and immune-enhancing effects. In this study, TRF supplementation was used as an adjuvant to enhance the anti-cancer effects of dendritic cells (DC)-based cancer vaccine in a syngeneic mouse model of breast cancer. Female BALB/c mice were inoculated with 4T1 cells in mammary pad to induce tumor. When the tumor was palpable, the mice in the experimental groups were injected subcutaneously with DC-pulsed with tumor lysate (TL) from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Tocotrienol isoforms inhibited proliferation of human breast cancer cells in the following order: αT3 < TRF < γT3 < δT3 [137]. In addition, daily supplementation of 1 mg of TRF was reported to inhibit tumor growth in a syngeneic murine model of breast cancer [31,124,137]. A similar observation was also reported in a xenograft athymic mouse model of breast cancer where a significant delay in the onset of breast cancer in mice fed with 1 mg TRF was observed [138].…”
Section: Tocotrienolsupporting
confidence: 58%
See 1 more Smart Citation
“…Tocotrienol isoforms inhibited proliferation of human breast cancer cells in the following order: αT3 < TRF < γT3 < δT3 [137]. In addition, daily supplementation of 1 mg of TRF was reported to inhibit tumor growth in a syngeneic murine model of breast cancer [31,124,137]. A similar observation was also reported in a xenograft athymic mouse model of breast cancer where a significant delay in the onset of breast cancer in mice fed with 1 mg TRF was observed [138].…”
Section: Tocotrienolsupporting
confidence: 58%
“…TRF contains three main isoforms of tocotrienol, which are αT3 (29%), γT3 (28%) and δT3 (14%) isomers [119]. Tocotrienols are reported to possess anti-thrombotic [120], antioxidant [121], neuroprotective [122] and cardio-protective [123] activities as well as immune modulatory [124,125] properties. Both cell-based and experimental model studies have suggested that tocotrienols also possess anti-tumor properties as these compounds can inhibit proliferation of many cancer cell lines including prostate [126], breast [127], skin [128], colon [129], stomach [130], pancreatic [131], liver [132] and lung [133] cancers.…”
Section: Tocotrienolmentioning
confidence: 99%
“…The bone marrow (BM) was harvested under aseptic conditions. The tibia and femur bones were obtained from euthanized BALB/c mice and the BM cells were obtained by flushing the cut tibia and femur bones with complete medium using a 22 cc needle syringe as described previously [19,24]. Complete medium (CM) consisted of RPMI 1640 media with 10% fetal bovine serum (FBS, heat-inactivated), 1% glutamine, and 1% penicillin-streptomycin (PenStrep) added.…”
Section: Generation Of Bone Marrow-derived Dendritic Cellsmentioning
confidence: 99%
“…A week after the last DC injection, the mice in all five study groups received a single injection of 4T1 cells (50 µL of 4T1 cells in phosphate-buffered saline (PBS)) into their mammary fat pad. As reported previously, the tumor was usually palpable on day 14 [21,24]. Tumor growth was monitored once a week by measuring the size of the primary tumor using a digital caliper.…”
Section: Treatment Of Micementioning
confidence: 99%
See 1 more Smart Citation